Research on the construction of English intelligent classroom based on Artificial Intelligence - Wu, Yong; Othman, Abdul Jalil; Saad, Mohd Rashid Mohd (Sycamore Global Publications LLC, 2018)
Aiming at prompting efficiency and effectiveness of English teaching, establishment of integrated English teaching intelligent classroom based on artificial intelligence is discussed in this paper. For English learning, merely language teaching is not enough, nor is merely language learning, and successful English should cultivate students' intercultural communication ability and integrate the social culture factors of a language into the language teaching for students. Successful English teaching is an important guarantee of successful intercultural communication, but in real life, there are many cases of communication misunderstanding and failure which are caused by the disconnection between language teaching and culture teaching. Though affective computing research has wide range of applications, many opening problems still exist. Due to the uncertainty of emotions, traditional machine learning algorithms may not handle this uncertain inference problem well while probability theory provides us with the basic foundation to model the uncertainty of emotions. This paper establishes integrated English teaching intelligent classroom based on artificial intelligence and proposes some suggestions, aiming to improve students' English learning performance and intercultural communication ability.